Adult exposure influences offspring response to ocean acidification in oysters - Parker, Laura M.; Ross, Pauline M.; O'Connor, Wayne A.; Borysko, Larissa; Raftos, David A.; Pörtner, Hans Otto (Global Change Biology, 2012)
It is essential to predict the impact of elevated Pco 2 on marine organisms and habitats to anticipate the severity and consequences of future ocean chemistry change. Despite the importance of carry-over effects in the evolutionary history of marine organisms, few studies have considered links between life-history stages when determining how marine organisms will respond to elevated Pco 2 , and none have considered the link between adults and their offspring. Herein, we exposed adults of wild and selectively bred Sydney rock oysters, Saccostrea glomerata to elevated Pco 2 during reproductive conditioning and measured the development, growth and survival response of their larvae. We found that elevated Pco 2 had a negative impact on larvae of S. glomerata causing a reduction in growth, rate of development and survival. Exposing adults to elevated Pco 2 during reproductive conditioning, however, had positive carry-over effects on larvae. Larvae spawned from adults exposed to elevated Pco 2 were larger and developed faster, but displayed similar survival compared with larvae spawned from adults exposed to ambient Pco 2 . Furthermore, selectively bred larvae of S. glomerata were more resilient to elevated Pco 2 than wild larvae. Measurement of the standard metabolic rate (SMR) of adult S. glomerata showed that at ambient Pco 2 , SMR is increased in selectively bred compared with wild oysters and is further increased during exposure to elevated Pco 2 . This study suggests that sensitive marine organisms may have the capacity to acclimate or adapt to elevated Pco 2 over the next century and a change in energy turnover indicated by SMR may be a key process involved.